2021
DOI: 10.3389/fneur.2021.695910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcutaneous Spinal Direct Current Stimulation (tsDCS) in Patients With Chronic Pain: A Clinical and Neurophysiological Study

Abstract: Background and Aims: Chronic pain is a complex clinical condition, often devastating for patients and unmanageable with pharmacological treatments. Converging evidence suggests that transcutaneous spinal Direct Current Stimulation (tsDCS) might represent a complementary therapy in managing chronic pain. In this randomized, double-blind and sham-controlled crossover study, we assessed tsDCS effects in chronic pain patients.Methods: Sixteen patients (aged 65.06 ± 16.16 years, eight women) with chronic pain of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 66 publications
2
23
2
Order By: Relevance
“…Contrary to what was suggested in previous experimental studies, our simulations therefore showed an sizable contribution of cutaneous fibers to the motor evoked potentials during cervical tSCS [17,52]. While cutaneous afferents may contribute to motor evoked potentials, they may also convey divergent excitatory potentials to relevant spinal nodes and significantly contribute to the rehabilitative potential of non-invasive spinal stimulation [5355]. Taken together, our results showed preferential recruitment of Aα- and Aβ-sensory fibers compared with α-motor fibers, suggesting large contribution of proprioceptive and cutaneous activations during cervical tSCS.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Contrary to what was suggested in previous experimental studies, our simulations therefore showed an sizable contribution of cutaneous fibers to the motor evoked potentials during cervical tSCS [17,52]. While cutaneous afferents may contribute to motor evoked potentials, they may also convey divergent excitatory potentials to relevant spinal nodes and significantly contribute to the rehabilitative potential of non-invasive spinal stimulation [5355]. Taken together, our results showed preferential recruitment of Aα- and Aβ-sensory fibers compared with α-motor fibers, suggesting large contribution of proprioceptive and cutaneous activations during cervical tSCS.…”
Section: Discussioncontrasting
confidence: 88%
“…However, it is important to note that other parameter selection such as the duration of stimulation [15] and voluntary involvement during stimulation [4] are likely required for effective neuromodulation during cervical spinal stimulation. Taken together, our findings imply that the activation of Aα- and Aβ-sensory fibers during cervical tSCS likely plays a role in motor rehabilitation of spinal cord injured patients [1,3,5], also suggesting potential utility of this technology for treatment of other clinical conditions such as sensorimotor impairment caused by stroke [53,54] and for chronic pain [55].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…With the aim to treat neuropathic pain due to PNP, we have studied one of the more novel, non-invasive paradigms; transcutaneous spinal direct current stimulation (tsDCS). The technique involves a low-intensity spinal stimulation and has been demonstrated to induce polarity-dependent effects on different pathways of the spinal cord, e.g., [6][7][8]. One promising effect is that of anodal tsDCS on pain signaling; in a double-blind, sham-controlled study on healthy subjects we have been able to reproduce and expand on prior studies [6,7] finding parallel inhibitory effects of anodal tsDCS on subjective pain experience and pain signaling [9].…”
Section: Introductionmentioning
confidence: 63%
“…Non-invasive trans-spinal cord direct current stimulation (tsDCS) has the potential for promoting spinal motor function through its modulatory actions on sensory processing ( Aguilar et al, 2011 ), reflexes ( Winkler et al, 2010 ; Song et al, 2015 ; Mekhael et al, 2019 ), the motor cortex motor map ( Ahmed, 2013a ; Song et al, 2015 ), and enhancing spinal motor circuit function and motor output ( Ahmed, 2011 ; Jankowska, 2017 ; Song and Martin, 2017 ). tsDCS has also been used for treating different neurological diseases and injuries (e.g., Picelli et al, 2015 and Lamy et al, 2021 ) and for pain control ( Guidetti et al, 2021 ). The effects of tsDCS tend to be polarity dependent.…”
Section: Introductionmentioning
confidence: 99%